Associations of common noncommunicable medical conditions and chronic diseases with chronotype in a population-based health examination study. (21st April 2017) - Basnet, Syaron; Merikanto, Ilona; Lahti, Tuuli; Männistö, Satu; Laatikainen, Tiina; Vartiainen, Erkki; Partonen, Timo
ABSTRACT: Chronotype is an emerging predictor of health and longevity, and understanding its influence on chronic diseases is important for constructing conceptual models of long-term pathways to health. We assessed the associations of chronotype with health status in the general Finnish adult population. Our population-based data were derived from the National FINRISK 2012 study and consisted of 4414 participants, aged 25–74 years, living in Finland. As part of their health examination, participants were asked about their circadian preference to the daily activities (morningness–eveningness) and a diagnosis or treatment for a set of common noncommunicable medical conditions and chronic diseases during the past 12 months. We found that there were 1935 (43.8%) morning types (MTs) and 595 (13.5%) evening types (ETs) and that 1884 (42.7%) were intermediates. As compared with the MTs, the ETs had significantly greater odds for depression (OR = 2.44, 95% CI = 1.52–3.90, p < 0.001) and other mental disorders (OR = 5.18, 95% CI = 2.32–11.52, p < 0.001). The odds were also increased for gallstones, and chronic obstructive pulmonary disease, but these did not remain significant after controlling for multiple testing. Responses to the single-item subjective estimation on the chronotype yielded the association of the definitely evening type of persons with the diagnosis or treatment of cardiac insufficiency (OR = 1.99, 95% CI = 1.02–3.88, p = 0.044) that was corroborated as the greater the eveningness score was, the more common the diagnosis or treatment of cardiac insufficiency was ( β = 0.92, 95% CI = 0.85–0.98, p = 0.013). This exploratory study adds further support to the role of evening chronotype in chronic disease risk, albeit underlying mechanisms remain to be elucidated.